New acute onset of ocular myasthenia gravis after COVID-19 vaccine: A case report - Himani T. Chaturvedi; Varsha Patel; Rahul Vasava; Chandrashekher Chaturvedi (Journal of Family Medicine and Primary Care)
Reports have shown the association of coronavirus disease 2019 (COVID-19) with several neuromuscular disorders. Myasthenia gravis (MG) is an autoimmune disease in which antibodies bind to acetyl choline receptors in the postsynaptic membrane at the neuromuscular junction. The characteristic clinical feature of the disease is weakness of the ocular muscle, bulbar muscle, and extremity muscles; when the weakness is limited to the ocular muscle only, the condition is known as ocular myasthenia gravis. Diagnosis is usually confirmed by the acetylcholine receptor antibodies. Symptoms of MG may be aggravated by various types of infections and medications. Here, we are presenting a rare case of a new and acute onset of ocular MG presented after administration of Covishield vaccine.